Factors Affecting Patient Safety Culture in Handling High Alert Medications - Hastuti, Dwi Siwi Murni (Lembaga Penerbitan Universitas Esa Unggul, 2025)
This research is based on observation results which show that in the ICU and inpatient rooms there are still problems regarding patient safety culture in handling high alert drugs. The aim of this research is to empirically reveal the influence of EMR implementation and interprofessional collaboration on patient safety culture in handling high alert drugs with work engagement as an intervening variable. This type of research is quantitative with a causality design. The population used was 110 inpatient installation nurses. The sampling technique used a saturated sample. The results of the analysis prove that EMR implementation and interprofessional collaboration have a positive and significant effect on patient safety culture in handling high alert drugs with work engagement as an intervening variable, EMR implementation and interprofessional collaboration have a positive and significant effect on work engagement and patient safety culture in handling high alert drugs , and work engagement has a positive and significant effect on patient safety culture in handling high alert drugs, as well as providing positive intervention on the influence of EMR implementation and interprofessional collaboration on patient safety culture in handling high alert drugs, so that with work engagement, EMR implementation and collaboration Interprofessionals can be more optimal in improving patient safety culture in handling high alert drugs.